1925
DOI: 10.1113/jphysiol.1925.sp002244
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the heat production during a contraction in which work is performed

Abstract: RECENT experiments by Fenn(l, 2) have shown that when a muscle is allowed to shorten and do work there is a further output of energy beyond that liberated in an isometric contraction. When the load was held by the muscle during contraction only, and not during relaxation, the total extra energy liberated was approximately equal to the work done, so that the energy liberated as heat was constant. If the load rested on the muscle during relaxation then still more heat was given out. It seemed desirable to consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1926
1926
1952
1952

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…That the relaxation heat does really represent mechanical potential energy dissipated during relaxation is confirmed by experiments [Hartree, 1925;Hartree and Hill, 1928] in which it has been shown that when work is done by a stimulated muscle the relaxation heat is correspondingly reduced. This mechanical energy is probably far less than the area of the tension-length curve [see Hartree and Hill, 1928, p. 13, etc.…”
Section: Initial Heat Production Of Musclementioning
confidence: 85%
See 1 more Smart Citation
“…That the relaxation heat does really represent mechanical potential energy dissipated during relaxation is confirmed by experiments [Hartree, 1925;Hartree and Hill, 1928] in which it has been shown that when work is done by a stimulated muscle the relaxation heat is correspondingly reduced. This mechanical energy is probably far less than the area of the tension-length curve [see Hartree and Hill, 1928, p. 13, etc.…”
Section: Initial Heat Production Of Musclementioning
confidence: 85%
“…Later, however, quicker thermopiles consisting of a single layer of thin wire were made, and the galvanometer was improved, the resulting analyses being much more definite. An example was published [Hartree, 1925], unfortunately without numerical details; these, however, have been supplied since [Hill, 1930a: Appendix by Hartree]. In various other investigations [e.g.…”
mentioning
confidence: 99%
“…The full amount of work cannot be done-owing to the " viscosity " of the muscle substance-unless the shortening be slow, unless, that is, the con ditions be, in the thermodynamic sense, reversible. Now, Hartree (16) found-in confirmation of Fenn-that in a frog's muscle allowed to shorten, doing or without doing work, the heat set free is the same as in an isometric contraction, an extra amount of energy being liberated to provide for the work, if any, performed. He ascertained, however, that when shortening was allowed there was 15 per cent, extra heat in the first (contraction) phase and a corresponding deficit in the second (relaxation).…”
Section: The Effect Of Doing Work Upon the Total Energy Exchangementioning
confidence: 90%
“…In a paper by Hartree and A. V. Hill to appear shortly, the manuscript of which was kindly shown to the writer, the view receives support that the truest measure of the mechanical potential energy is the heat liberated in relaxation, rather than the tension length diagram area as used by A. V. Hill (35) and others before. Such a view, for which Meyerhof (38) has always contended, upon other grounds, however, has received this new support as a result of further investigation of the Fenn effect (36,37). The determination of the theoretical maximum work is further complicated and rendered un certain by the possibility suggested by A. V. Hill (35, p. 261, lines 18-21) and later by Wyman (39), that part of the potential energy of tension may be used in reconversion processes rather than all being converted quantitatively into heat.…”
Section: Comparison Of Observed and Calculated Free Energiesmentioning
confidence: 99%